Definition Matters : Metropolitan Areas and Agglomeration Economies in a Large Developing Country - Bosker, Maarten; Park, Jane; Roberts, Mark (World Bank, Washington, DC, 2019)
A variety of approaches to delineate metropolitan areas have been developed. Systematic comparisons of these approaches in terms of the urban landscape that they generate are however few. Our paper aims to fill this gap. We focus on Indonesia and make use of the availability of data on commuting flows, remotely-sensed nighttime lights, and spatially fine-grained population, to construct metropolitan areas using the different approaches that have been developed in the literature. We find that the maps and characteristics of Indonesia’s urban landscape vary substantially depending on the approach used. Moreover, combining information on the metro areas generated by the different approaches with detailed micro-data from Indonesia’s national labor force survey, we show that the estimated size of the agglomeration wage premium depends nontrivially on the approach used to define metropolitan areas.